Pelatihan Smart PLS Bagi Para Peneliti Akuntansi dan Bisnis di Universitas Binaniaga Indonesia - Sitorus, Riris Rotua (Jurnal Pemberdayaan Nusantara, 2024)
The purpose of this training is to educate accounting and business researchers at Binaniaga Indonesia University, on how to process research data in accounting and business using Smart PLS software. Primarily how to run data based on structural equation modeling, which consists of intervening models and moderating models. There are two methods used, the first is the lecture method for explaining concepts and theories. Second, the method of practical data processing. The number of participants who filled out the evaluation form was 20 participants. The evaluation instrument used was questions on the Google form related to understanding the training material. The evaluation results showed an increase in the participants' abilities. First, an increase in the ability to prepare excel csv data and data input skills, as well as the ability to draw research models. Second, an increase in the ability to conduct validity and reliability tests, as well as the reduction process for invalid questions. Third, an increase in the ability to evaluate r square and goodness of fit, as well as compiling structural equations. Fourth, the ability to test the intervening SEM model, as well as the interpretation of direct and indirect effects. Fifth, the ability to test the moderating SEM model, as well as the interpretation of the moderating effect.